2020
DOI: 10.21203/rs.3.rs-54054/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Prevalence, Risk Factors and Prognosis of Acute Kidney Injury after Lung Transplantation: A Single-center Cohort Study in China

Abstract: Background To evaluate the incidence, risk factors, and prognosis of acute kidney injury (AKI) after lung transplantation (LTx). Methods Records of patients who underwent LTx in a single center were retrospectively reviewed. The prevalence of post-transplant AKI, the use of continuous renal replacement therapy (CRRT), and the risk factors for AKI were investigated. The impact of AKI and CRRT on short-term outcomes and long-term survival was measured. Results 148 patients were included with 67 cases develope… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The authors provided the preoperative comorbidities of patients, but not an assessment of overall health status and acute illness conditions before surgery. The available evidence indicates that preoperative higher acute physiologic assessment and chronic health evaluation (APACHE) II scores are the independent risk factors of AKI in patients undergoing lung transplantation [3]. Furthermore, a higher lung allocation score at transplantation, preoperative mean pulmonary artery pressures greater than 35 mm Hg, ICU stay before transplantation and preoperative use of extracorporeal membrane oxygenation or mechanical ventilation have been significantly associated with the occurrence of AKI following lung transplantation [4].…”
Section: Letter To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…The authors provided the preoperative comorbidities of patients, but not an assessment of overall health status and acute illness conditions before surgery. The available evidence indicates that preoperative higher acute physiologic assessment and chronic health evaluation (APACHE) II scores are the independent risk factors of AKI in patients undergoing lung transplantation [3]. Furthermore, a higher lung allocation score at transplantation, preoperative mean pulmonary artery pressures greater than 35 mm Hg, ICU stay before transplantation and preoperative use of extracorporeal membrane oxygenation or mechanical ventilation have been significantly associated with the occurrence of AKI following lung transplantation [4].…”
Section: Letter To the Editormentioning
confidence: 99%
“…Thus, it is difficult to determine the extent of influence that anesthesiologists' interventions may have on the occurrence of postoperative AKI. Other than transplant types, operation duration, intraoperative extracorporeal membrane oxygenation support and blood loss provided by the authors, the recent works have shown that intraoperative increased fluid balance, use of vasoactive drugs, hypoxemia, severe arterial hypotension with hemodynamic decompensation are significantly associated with an increased risk of AKI after lung transplantation [3,5]. Indeed, multivariate analysis is useful for the identification of risk factors of adverse perioperative events by adjusting patients' baseline characteristics and controlling selection biases in a retrospective study.…”
Section: Letter To the Editormentioning
confidence: 99%